Analisis Kesesuaian Lahan SPBU di Bandar Lampung Menggunakan Sistem Informasi Geografis - Vanisa Aufa Maharani; Meraty Ramadhini; Misfallah Nurhayati; Muhammad Ario Eko Rahadianto; Een Lujainatul Isnaini (Jurnal Inotera, 2023)
Bandar Lampung is identified as one of the densely populated urban center in Indonesia. As the population increases, the ownership of motorized vehicles using gasoline is also on the rise. This has led to a growth in the construction of fuel stations, which needs to be examined from various aspects, one of which is land suitability. This research aims to identify the distribution of fuel stations, determine the parameters used, and analyze the level of suitability of fuel stations in Bandar Lampung. The spatial data used in this study includes the National Spatial Plan of Bandar Lampung for the period 2021-2041 and the coordinates of fuel stations in Bandar Lampung. Additionally, non-spatial data such as questionnaire results and field validations are also utilized. The methods applied are the Analytical Hierarchy Process (AHP) and overlay. Based on the results obtained, there are 33 fuel station scattered across 17 out of 20 districts in Bandar Lampung and there are three districts that do not yet have fuel stations namely Tanjung Karang Barat, Tanjung Karang Timur, and Teluk Betung Barat. The parameters used in this study are four: road function, distance between fuel stations, distance of fuel stations to residential areas, and areas prone to landslide disasters. The level of suitability of fuel stations is classified into three categories: highly suitable, suitable, and less suitable. Out of the 33 fuel stations, 32 are classified as very suitable, and 1 is classified as suitable.